Digital ethics education for responsible social media use among junior high school students at MTs Al Furqan: A participatory community service program - Galih Abdul Fatah Maulani; Muhamad Fathur Fawwaz; Sopa Siti Marwah; Azriel Aldika; Ali Ahmad Hanafiah; Restu Ardiansyah (Nur Science Institute, 2026)
Digital ethics education is increasingly needed as adolescents use social media for communication, entertainment, and learning while also facing risks related to hoaxes, cyberbullying, privacy leakage, and impolite online interaction. This article reports a participatory community service program at MTs Al Furqan aimed at strengthening students’ knowledge and awareness of responsible social media use. The program involved 87 seventh- and eighth-grade students in 2025. The activities consisted of partner needs identification, an interactive seminar, guided discussion, roleplay simulation, and pretest–posttest evaluation. The pretest showed an average score of 42.3%, indicating limited initial understanding, especially in preventive actions against social media risks (13.7%). After the program, the average posttest score increased to 83.7%, with the highest achievements in hoax response (100%), recognizing shareable information (90.8%), and understanding social media risks (89.6%). These findings indicate that participatory digital ethics education can strengthen students’ digital literacy, online safety awareness, and practical readiness to respond to hoaxes, cyberbullying, and privacy risks.